Strategies for Improving Teacher Competence at Darussalam Modern Islamic Boarding School Gontor - Syarifah, Muwahidah Nurhasanah, Saiful Anwar, Saepul Anwar, Irvan Hidayat (STAI Syaichona Moh. Cholil Bangkalan, 2025)
This study aims to analyze strategies for improving teacher competency at the Darussalam Gontor Modern Islamic Boarding School in Ponorogo.The focus of this research is to explore the various efforts undertaken by management to improve teacher quality through various programs, such as training, in-depth material, and weekly evaluations. The method used in this study is a qualitative approach with a descriptive design, with data collected through interviews, observation, and documentation. The results of the study indicate that the management of the Darussalam Gontor Islamic Boarding School has successfully created a systematic program to improve teacher competency, despite several inhibiting factors, such as difficulties in managing teachers' time.